Urban Decay in Central Hill, Port Elizabeth. (June 2019) - Swanepoel, F; Smallwood, J
Abstract: Urban decay has caused the destruction of many neighbourhoods in many great cities, and Central Hill in Port Elizabeth is no exception. Given the reports in the media, and the visible urban decay in areas of Central Hill, a qualitative study entailing interviews was undertaken to determine the status quo, and the relationship, if any between various issues relating to urban decay. Findings include: that urban regeneration has had an impact, however urban decay is still occurring; there are five key issues in terms of mitigating urban decay through the management of the area; there are thirteen qualities that make a building uninhabitable; the raiding of abandoned buildings cause urban decay; there are five key aspects of a building require regular maintenance, and building owners can receive enough income to maintain their buildings if they ask fair market related rentals. Conclusions include that the cause of urban decay cannot be pinned to one specific event or incident, but is a result of many factors. Recommendations include: the development of an overarching strategy; optimum management of the area by all stakeholders; optimum policing; adequate maintenance of buildings; market-related rentals; development and enforcement of municipal bylaws, and municipal incentives for maintaining buildings in an optimum state.